2022
DOI: 10.31219/osf.io/j7k4w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Influencing the Political Activity of Social Workers: A Comparative Study Among Swiss and United States Social Workers

Abstract: Various international and national social work ethical principles call social workers to participate in politics, yet not much research exists in the field of a political so-cial work. Little is known about the actual voluntary political engagement of social workers as well as factors influencing their political activity. Especially, few stud-ies with an international comparison focus have been conducted. Consequently, this study used cross sectional survey design to better understand the factors in-fluencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In recent years, there are signs of more theoretically driven and systematic empirical efforts to identify the factors that explain SWs' policy engagement in the different policy routes (Gal and Weiss-Gal, 2015;Guidi, 2020;Kindler and Ostrander, 2022). The policy engagement conceptual framework (Gal and Weiss-Gal, 2023) provides a useful way to describe this volume of research and to present the factors that the research identified.…”
Section: Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there are signs of more theoretically driven and systematic empirical efforts to identify the factors that explain SWs' policy engagement in the different policy routes (Gal and Weiss-Gal, 2015;Guidi, 2020;Kindler and Ostrander, 2022). The policy engagement conceptual framework (Gal and Weiss-Gal, 2023) provides a useful way to describe this volume of research and to present the factors that the research identified.…”
Section: Explanationsmentioning
confidence: 99%
“…In particular, scholars have underscored the impact of civic or political skills, a psychological engagement with politics (self-efficacy to engage in politics or political interest) and membership in recruitment networks on policy engagement. This was the case for VPP (Ritter, 2008;Kindler and Ostrander, 2022), running for elected office (Lane and Humphreys, 2011;Greco, 2020;Amann and Kindler, 2022;Binder and Weiss-Gal, 2022), PP (Weiss- Gal and Gal, 2020) and a readiness of SWs to participate in the policy activities of SWPOs (Hoefer et al, 2019).…”
Section: Explanationsmentioning
confidence: 99%